2017
DOI: 10.2741/4552
|View full text |Cite
|
Sign up to set email alerts
|

Endocytosis and membrane receptor internalization implication of F-BAR protein Carom

Abstract: Endocytosis is a cellular process mostly responsible for membrane receptor internalization. Cell membrane receptors bind to their ligands and form a complex which can be internalized. We previously proposed that F-BAR protein initiates membrane curvature and mediates endocytosis via their binding partners. However, F-BAR protein partners involved in membrane receptor endocytosis and the regulatory mechanism remain unknown. In this study, we established a group of database mining strategies to explore mechanism… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(10 citation statements)
references
References 65 publications
(74 reference statements)
0
10
0
Order By: Relevance
“…We have selected hsa_circ_0000338 for functional analysis to elucidate its possible role in chemoresistance. Hsa_circ_0000338 is a circRNA derived from gene FCHSD2 that encodes for a protein involved in endocytosis and membrane receptor internalization 66 . Genome-wide association studies identified FCHSD2 as a novel susceptibility gene for Crohn’s disease in Korean and Japanese populations 67,68 .…”
Section: Discussionmentioning
confidence: 99%
“…We have selected hsa_circ_0000338 for functional analysis to elucidate its possible role in chemoresistance. Hsa_circ_0000338 is a circRNA derived from gene FCHSD2 that encodes for a protein involved in endocytosis and membrane receptor internalization 66 . Genome-wide association studies identified FCHSD2 as a novel susceptibility gene for Crohn’s disease in Korean and Japanese populations 67,68 .…”
Section: Discussionmentioning
confidence: 99%
“…Normally, secreted pro-enzymes are taken up by the IGF2R/M6P receptor, formed pro-enzyme/ IGF2R/M6P complexes are then internalized through clathrin-mediated endocytosis (Figure 9) [39]. Monensin and chloroquine have been used to inhibit the initial step of clathrin-dependent endocytosis: formation of the clathrin-coated pit to the clathrin-coated vesicles [40]. We showed that inhibition of initiation of clathrin-coated vesicles resulted in a significant blockade of the transport of recombinant enzyme to HEK293, HUVEC, fibroblasts, and UKEC cells.…”
Section: Discussionmentioning
confidence: 99%
“…Similar to other cell surface receptors (26), TGF-β receptors are mainly internalized via clathrin-dependent endocytosis, which is an essential regulatory event in signal transduction (27,28). In addition, lipid rafts/caveolae negatively regulate TGF-β1 signaling pathway through lipid raft-induced internalization of TGF-β receptors, promoting receptor degradation (29).…”
Section: Discussionmentioning
confidence: 99%